Pengaruh Locus of Control Terhadap Motivasi Belajar Siswa - La Kalamu, La Yusran (KAMBOTI: Jurnal Sosial dan Humaniora, 2021)
Motivation to learn can be interpreted as a desire that arises in a person to carry out learning activities in order to obtain the expected goals. This desire comes from outside yourself or comes from within a person. One of the internal factors that influence learning motivation is locus of control (LoC). LoC is a person's self-control towards the success he achieves in his daily activities. The purpose of this study was to determine the direct effect of LoC on student learning motivation. This type of research is a causal survey with path analysis type. The number of research samples were 95 students who were selected by multistage random sampling randomly from 1729 students. The results of the study of LoC variables and learning motivation were collected through an attitude scale then processed statistically. The description of the results of the student learning motivation data reached an average of 121.97, the standard deviation value was 121.97, the mode value was 114.77, the median value was 118.39; with 43 students (45%) obtaining scores below the mean interval. It was obtained that 34 students (36%) obtained the value lies in the average interval score, as many as 18 students (19%) achieved a value above the average interval. The results of the independent variable data (LoC) achieved an average value of 150.89, a median value of 158, 57, a mode value of 146.64 and a standard deviation of 25.53, with 42 students (44%) obtaining a score below the average interval . As many as 19 students (20%) obtained scores that were located on the average interval, then 34 students (36%) obtained scores above the average interval. Based on the results of data analysis, it is concluded that LoC has a positive direct effect on the learning motivation of students at State Junior High Schools in Gorontalo City. The creation of student learning motivation is influenced by their LoC.